2010
DOI: 10.1177/0040517509358798
|View full text |Cite
|
Sign up to set email alerts
|

Skin Delivery of Caffeine Contained in Biofunctional Textiles

Abstract: Biofunctional textiles are materials with new properties and added value. In this work, emphasis was placed on the release capacity of the active principle (caffeine) from the formulation or from the biofunctional textile. In addition, a new in vitro methodology of percutaneous absorption was designed to demonstrate the delivery of encapsulated caffeine from the biofunctional textile to the different skin layers. In the first step, permeation studies through a nylon membrane were performed and the release capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
(13 reference statements)
0
18
0
Order By: Relevance
“…Using the in vitro methodology of percutaneous absorption, it is possible to detect the amount of the active principle that penetrates each skin layer from a given cosmeto-textile [27]. It is reasonable to assume that the reservoir capacity of a cosmeto-textile, close contact with the skin and the corresponding skin occlusion may be the main factors that determine how an active principle (e.g., GA) crosses the skin barrier, located in the stratum corneum, and penetrates the different compartments of the skin.…”
Section: /12mentioning
confidence: 99%
“…Using the in vitro methodology of percutaneous absorption, it is possible to detect the amount of the active principle that penetrates each skin layer from a given cosmeto-textile [27]. It is reasonable to assume that the reservoir capacity of a cosmeto-textile, close contact with the skin and the corresponding skin occlusion may be the main factors that determine how an active principle (e.g., GA) crosses the skin barrier, located in the stratum corneum, and penetrates the different compartments of the skin.…”
Section: /12mentioning
confidence: 99%
“…According to the OECD methodology [20], the skin penetration studies were performed for 24 h of close contact between the textile and the skin. To increase the contact pressure between the textile fabric and skin, permeation experiments were also carried out by placing a steel cylinder on the textile-skin substrate at a constant pressure in accordance with standard conditions (125 g/cm 2 ) (ISO 105-E04, 1996) [21] (see Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…Differences in the application time on human ex vivo skin (24 h) could also account for this finding. Rubio et al [32] reported a percutaneous absorption of caffeine into the tissue of 1% by applying a liquid caffeine formulation. It can be summarized that the achieved recovery in the dermis is comparable to the published data.…”
Section: Study Design B: Investigation Of the Influence Of Follicularmentioning
confidence: 99%